Methodology of intellectual property management processes - Maslak, M. V. (Wyższa Szkoła Ekonomiczno-Humanistyczna, Poland, 2023)
The article proves that the management of intellectual property is a set of management actions carried out by an industrial enterprise in order to ensure the implementation of the legal system of intellectual property and protect the legal rights and interests of subjects of intellectual property law, as well as natural persons. Intellectual property right enables property owners to maximize the economic and social benefits of their intellectual achievements. It is justified that the content of intellectual property management corresponds to the system of intellectual property protection. Only after understanding the content of the intellectual property system, can we find out the content of intellectual property management and scientifically build and operate the intellectual property management system at industrial enterprises.
Методологія процесів управління інтелектуальною власністю
Keywords: intellectual property; management; methodology; essence; use; disposition; legal protection; legal protection